2011
DOI: 10.4102/jsava.v82i4.74
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic changes in Thoroughbred yearlings in South Africa

Abstract: This study involves the evaluation of pre-purchase radiographic studies of South African Thoroughbred yearlings. Radiographic changes were recorded and compared with similar international studies. The study differs from other studies in that a lower prevalence of pedal osteitis (1.26 %), dorsal osteochondral fragmentation of the metatarsophalangeal joint (1.60 %), distal metacarpal sagittal ridge changes (15.7 %), ulnar carpal bone lucencies (8.33 %), carpal osteophytes (1.19 %), distal intertarsal and tarsome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The prevalence of FDDT is similar to that of OCD of the LTR and/or MTR of the talus, and of OCD of the medial malleolus of the tibia in previous studies. 4,6,[7][8][9][10][11]13 The prevalence of OCD of the DIRT in the current study (5.01%) was 7.95-fold greater than that of FDDT lesions and was similar to that previously reported in Australian yearlings 7,9,11 and in yearling populations in the USA, 4,13 France, 14 South Africa, 8 New Zealand 6 and Japan. 10 However, the true prevalence is likely to be underestimated in studies in which surgical removal of lesions before repository examination is not reported.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of FDDT is similar to that of OCD of the LTR and/or MTR of the talus, and of OCD of the medial malleolus of the tibia in previous studies. 4,6,[7][8][9][10][11]13 The prevalence of OCD of the DIRT in the current study (5.01%) was 7.95-fold greater than that of FDDT lesions and was similar to that previously reported in Australian yearlings 7,9,11 and in yearling populations in the USA, 4,13 France, 14 South Africa, 8 New Zealand 6 and Japan. 10 However, the true prevalence is likely to be underestimated in studies in which surgical removal of lesions before repository examination is not reported.…”
Section: Discussionsupporting
confidence: 87%
“…3 Studies have assessed the prevalence of some of these findings in juvenile Thoroughbreds [3][4][5][6][7][8][9][10][11] and their association with race performance 5,10,12-14 although evaluation of uncommon lesions has been limited by the low power of some studies. With expert interpretation, these examinations can highlight abnormalities that may affect sale, soundness and performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Veterinarians are required to interpret the significance of radiographic findings for sale, soundness and future racing performance . Studies have assessed the prevalence of some of these radiographic changes and their association with subsequent performance, although limitations associated with these studies, including the low power of those that have evaluated less common lesions, have been recognised …”
mentioning
confidence: 99%
“…Because radiographic abnormalities can decrease the contract price and sometimes these abnormalities are needed medical management of a horse, the prevalence of these abnormalities and the effects of these abnormalities on their future performances should be investigated. The prevalence of radiographic abnormalities at the time of yearling sales has already been reported in the U.S.A. [ 9 ], Australia [ 8 ], New Zealand [ 13 ] and South Africa [ 6 ], but not in Japan.…”
mentioning
confidence: 99%